Serum Calprotectin Versus Acute‐Phase Reactants in the Discrimination of Inflammatory Disease Activity in Rheumatoid Arthritis Patients Receiving Tumor Necrosis Factor Inhibitors. Issue 7 (July 2016) - Inciarte‐Mundo, José; Victoria Hernández, Maria; Ruiz‐Esquide, Virginia; Raquel Cabrera‐Villalba, Sonia; Ramirez, Julio; Cuervo, Andrea; Pascal, Mariona; Yagüe, Jordi; Cañete, Juan D.; Sanmarti, Raimon
Abstract : Objective: To compare the accuracy of serum calprotectin and acute‐phase reactants (C‐reactive protein [CRP] and erythrocyte sedimentation rate [ESR]) in stratifying disease activity in rheumatoid arthritis (RA) patients receiving tumor necrosis factor inhibitors (TNFi), and to correlate calprotectin levels with TNFi trough serum levels. Methods: We conducted a cross‐sectional study of 87 RA patients receiving adalimumab, etanercept (ETN), or infliximab (IFX); 56 psoriatic arthritis (PsA) patients and 40 healthy blood donors were included as controls. Associations between calprotectin, CRP, and ESR and composite articular indices (Disease Activity Score in 28 joints [DAS28], Simplified Disease Activity Index [SDAI], and Clinical Disease Activity Index) were analyzed by correlation and linear regression and the accuracy and discriminatory capacity of calprotectin by receiver operator characteristic curves (area under the curve [AUC]). Results: Calprotectin levels correlated better with all composite activity indices than CRP and ESR (all r coefficients >0.70). Calprotectin levels were significantly lower in RA and PsA patients in clinical remission compared with those with low disease activity for all articular indices. In RA, ESR discriminated between remission and low disease activity only when using DAS28, and CRP only with SDAI. In RA patients in remission/low disease activity, calprotectin but not CRP or ESR distinguished between patients with no swollen joints and those with ≥1 swollen joint (1.74 μg/ml versus 3.04 μg/ml; P = 0.010). Using DAS28 ≥2.6 as the reference variable, calprotectin showed an AUC of 0.92; the best cutoff was ≥2.47 μg/ml with a likelihood ratio of 6.3 (95% confidence interval 2.5–15.8). Calprotectin serum levels inversely correlated with trough serum drug levels of ETN (ρ = −0.671, P < 0.001) and IFX (ρ = −0.729, P = 0.017). Conclusion: Calprotectin may more accurately discriminate disease activity in RA patients receiving TNFi than acute‐phase reactants, even in patients with low inflammatory activity.